Pendapatan Usaha Mikro dalam Menghadapi Persaingan Ritel Modern: Studi Kasus Toko Cahaya Bone di Kelurahan Lamonae Kecamatan Wiwirano Kabupaten Konawe Utara - Murniati Murniati (INDO PUBLISHING, 2026)
The expansion of modern retail is often feared to affect the performance of micro-businesses, particularly threatening the income and business sustainability at the local level. This study aims to analyze micro-business income in the face of modern retail competition, taking a case study at Toko Cahaya Bone in Lamonae Village, Wiwirano District, North Konawe Regency. This research uses a quantitative approach with descriptive analysis methods. The data used is secondary data in the form of gross circulation (gross income) reports of Toko Cahaya Bone during the period of 2022 to 2024. The results showed that the business's gross circulation experienced a consistent increase. The total gross circulation was recorded at Rp2,250,000,000 in 2022, increased to Rp2,385,000,000 in 2023, and rose again to reach Rp2,650,000,000 in 2024. In conclusion, the presence of modern retail does not always have a negative impact on micro-business income. Micro-businesses are able to survive by utilizing business closeness with local consumers, social relationships, and flexibility in adjusting products according to market needs, which become their advantages in social capital and relational marketing.Keywords: Income, Micro Business, Modern Retail, Gross Circulation, Social Capital..